Strategy scout : how to deal with complexity and politics during strategy development - Kolbusa, Matthias (Management for Professionals, 2013)
There is a much better chance to politically establish a strategy in your company if strategy development is already tactically thought-out and all involved persons are included in an intelligent manner. This book demonstrates how to shape this process to ensure that a sustainable strategy is generated that provides economic stability, uniquely positions the company and can readily be implemented. After all, strategy for its own sake is worthless - what counts is implementation and results. The centre stage of strategy process is taken by the intelligent use and combination of methodological tools. Numerous case studies from enterprises and medium-sized businesses illustrate strategy work in a vivid and clear manner.